KEPUASAN HUBUNGAN ANTARA DETERMINASI DIRI TERHADAP PENYESUAIAN DIRI PADA BINTARA REMAJA DI DITSAMAPTA - Alice Zellawati; Laila Shofatin Nimah; Brigitan Argasiam (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2021)
This research aims to determine the relationship between self-determination and self-adjustment among Youth Non-Commissioned Officers at the Central Java Regional Police Ditsamapta. The population in this study were all members of the Central Java Regional Police Ditsamapta youth non-commissioned officers, totaling 115 people. The sampling technique used was purposive sampling. The sample size was 85 people because 30 were female teenage non-commissioned officers (Polwan). Data analysis in this study used Spearman correlation analysis. This research uses a psychological scale data collection method in the form of a Likert scale which consists of two scales, namely, a 24-item self-determination scale (? = 0.957) and a 24-item self-adjustment scale (? = 0.963). Based on the hypothesis proposed, namely